PENGARUH KUALITAS SISTEM, KUALITAS LAYANAN DAN KUALITAS INFORMASI TERHADAP KEPUASAN PENGGUNA SISTEM APLIKASI KEUANGAN TINGKAT INSTANSI (SAKTI) - Jus Samuel Sihotang (Jurnal Akuntansi Bisnis dan Publik, 2020)
This research dealt with four variables, namely system quality, service quality, information quality and user satisfaction. The aim of this research was to know whether there was an effect of system quality, service quality and information quality to SAKTI user satisfaction. The sample of this research was 83 staffs in KPPN North Sumatera who uses SAKTI. The research data was analyzed by using Multiple Linear Regression Analysis which was calculated by SPSS 2.2. From the data analysis, it was found that the implementation of SAKTI applications empirically has been successful. Based on four proposed hypotheses, all of them are proven and accepted. The service system affected the highest value. It also showed that there was a positive effect of system quality, service quality and information quality to SAKTI user satisfaction. To sum up, It is essential to strengthen and expand the SAKTI as an effort to improve the quality and accountability of integrated state financial management.